Qualitative Analysis of Hydroxyurea - Stéfanno Souza Santos; Isis Gomes dos Santos; Cinara Vanconcelos da Silva; Edith C L Cazedey (Drug Analytical Research, 2020)
Hydroxyurea (HU) is a cytostatic agent with antineoplastic activity and it has great clinical efficacy in the treatment of sickle cell disease. HU is part of the National Relation of Essential Medicines of Brazil and despite of its clinical importance, only the Portuguese, American and European Pharmacopoeias present monographs for this medicine. This study aimed to develop qualitative methods for identification and verification of purity of HU. For the HU identification, IR and UV spectroscopy were used, as well as TLC. The IR and UV spectra showed compatibility and the maximum absorption at 213 nm. For TLC, various pure or polarity gradient solvents were tested with results satisfactory for a mobile phase containing acetone and ethyl acetate (99:1, v/v). The replacement of the mobile phase generated less chemical waste, while minimizing the risks to the health of the operator, in accordance with the main concept of green analytical chemistry.